Active source seismic experiment peers under Soufrière hills volcano - Mattioli, Glen. (2012)
Characterizing internal structures of active volcanoes remains an enigmatic issue in geosciences. Yet studies of such structures can greatly improve hazard assessments, helping scientists to better monitor seismic signatures, geodetic deformation, and gas emissions, data that can be used to improve models and forecasts of future eruptions.